The Lucky Shamrock [large type] - Brown, Carolyn, 1948- (Center Point Large Print, 2023)
"Family doesn't mean everyone has to like each other. That's the case when cousins Taryn, Anna Rose, and Jorja return to Shamrock, Texas, to help manage their grandmother's flower shop, the Lucky Shamrock. The reunion isn't exactly a beautiful arrangement -- considering they're as compatible as ranchers and coyotes. Thank heaven for a handsome go-between like Clinton, who lives above the shop. The easygoing war vet, and most eligible bachelor in Wheeler County, is now throwing romance into the mix and setting the local women to gossiping. But as the hot months wear on, hidden secrets begin to surface for the temperamental Irish trio. And it's bringing them closer together than they ever thought possible. With a flurry of weddings, a love story in the making, a surprise baby, and crazy good fortune, maybe that shamrock painted on the window does bring luck. Because for Taryn, Anna Rose, and Jorja, this could be the summer that'll change their lives forever" --